Accretion and outflow in black-hole x-ray binaries - Dusoye, Avishek (Department of Astronomy, 2015)
Black hole X-ray binaries (BHXBs) are stellar binary systems consisting of a black hole (BH) and a companion star. They are known to produce X-ray emission through the accretion of mass from the companion star onto the black hole via an accretion disc, as well as radio emission originating from their jets. My thesis splits into two projects. On one hand, I focus on the connection between the X-ray emitting accretion disc and the radio jets of BHXBs in general, by studying the quasi-simultaneous evolution of the radio fluxes and the X-ray fluxes from 17 BHXBs. This connection, also known as the radio/X-ray correlation has been studied and updated over the past years. New observations of new and known sources have shown that another population of X-ray binaries exists (referred to as outliers), lying below the standard radio/X-ray correlation. I investigate whether the mass of the black hole component of BHXBs can explain the existence of these outliers. In my second project, I focus on an exotic source, known as SS433. It has a supercritical accretion disc and displays precessing relativistic jets. I investigate whether these jets are made up of proton-electron plasma or electron-positron plasma. Circular polarization (CP) is a good diagnostics for understanding the particle composition of radio jets. Therefore we have observed the circular polarized flux densities of SS433 using the Australia Telescope Compact Array (ATCA) for a broad range of frequencies between 1:4 - 10 GHz. From those observations, a CP spectrum can be constructed and the spectral index can be estimated. There are 4 ways of producing CP emission and the spectral index helps us to constrain the CP production mechanism. In addition, the kinematics of propelling a proton-electron plasma in a jet is different from that of electronpositron plasma. I simulate various plausible models for the energy content of the jets and thereby aim to constrain the particle composition of the jets. Black hole X-ray binaries (BHXBs) are stellar binary systems consisting of a black hole (BH) and a companion star. They are known to produce X-ray emission through the accretion of mass from the companion star onto the black hole via an accretion disc, as well as radio emission originating from their jets. My thesis splits into two projects. On one hand, I focus on the connection between the X-ray emitting accretion disc and the radio jets of BHXBs in general, by studying the quasi-simultaneous evolution of the radio fluxes and the X-ray fluxes from 17 BHXBs. This connection, also known as the radio/X-ray correlation has been studied and updated over the past years. New observations of new and known sources have shown that another population of X-ray binaries exists (referred to as outliers), lying below the standard radio/X-ray correlation. I investigate whether the mass of the black hole component of BHXBs can explain the existence of these outliers. In my second project, I focus on an exotic source, known as SS433. It has a supercritical accretion disc and displays precessing relativistic jets. I investigate whether these jets are made up of proton-electron plasma or electron-positron plasma. Circular polarization (CP) is a good diagnostics for understanding the particle composition of radio jets. Therefore we have observed the circular polarized flux densities of SS433 using the Australia Telescope Compact Array (ATCA) for a broad range of frequencies between 1:4 - 10 GHz. From those observations, a CP spectrum can be constructed and the spectral index can be estimated. There are 4 ways of producing CP emission and the spectral index helps us to constrain the CP production mechanism. In addition, the kinematics of propelling a proton-electron plasma in a jet is different from that of electron-positron plasma. I simulate various plausible models for the energy content of the jets and thereby aim to constrain the particle composition of the jets.